The Relationship Between the God Locus of Health Control and Halal Awareness Based on Demographic Factors - Nursanita, Nursanita; Faruqi, Faris; Hendryadi, Hendryadi; Suryani, Suryani; Iskandar, Donant Alananto; Fathoni, Muhammad Anwar (IQTISHADIA, 2025)
This study explores the relationship between the God Locus of Health Control (GLHC) and halal awareness in tourist destinations, with demographics such as gender, age, and education serving as differentiators. The sample consisted of 478 respondents selected through convenience sampling techniques, and data were collected using online questionnaires. The analysis was conducted using structural equation modeling (SEM) and multi-group analysis (MGA), which are robust statistical methods that examine complex relationships and comparisons among different demographic groups. The results indicate that GLHC is positively associated with halal awareness. Moreover, the relationship between GLHC and halal awareness was confirmed to be more dominant in men, the 25-30-year age group, and respondents with a master's and bachelor's degree. This study contributes to halal awareness research by introducing GLHC as a spiritual determinant, exploring demographic moderators (gender, age, education), and focusing on halal tourism, expanding beyond traditional product categories like food and cosmetics.